A simple protocol for tuberculin skin test reading certification - Lara de Lima Gloria; Mayara Lisboa Bastos; Bráulio dos Santos Júnior; Anete Trajman (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Although tuberculosis preventive therapy is one of the cornerstones for eliminating the disease, many barriers exist in the cascade of care for latent tuberculosis infection, including the need to certify healthcare professionals for reading tuberculin skin tests (TST). This paper proposes and evaluates a simple protocol for TST reading training. Primary care workers from different backgrounds received a 2-hour theoretical course, followed by a practical course on bleb reading. Blebs were obtained by injecting saline into sausages and then in volunteers. A certified trainer then evaluated the effectiveness of this protocol by analyzing the trainees' ability to read TST induration in clinical routine, blinded to each other's readings. Interobserver agreement was analyzed using the Bland-Altman test. The trainees' reading accuracy was calculated using two cut-off points - 5 and 10mm - and the effect of the number of readings was analyzed using a linear mixed model. Eleven healthcare workers read 53 saline blebs and 88 TST indurations, with high agreement for TST reading (0.07mm average bias). Sensitivity was 100% (94.6; 100.0) at 5mm cut-off and 87.3% (75.5; 94.7) at 10mm cut-off. The regression model found no effect of the number of readings [coefficient: -0.007 (-0.055; 0.040)]. A simple training protocol for reading TST with saline blebs simulations in sausages and volunteers was sufficient to achieve accurate TST induration readings, with no effect observed for the number of readings. Training with saline blebs injected into voluntary individuals is safer and easier than the traditional method.